2022
DOI: 10.3390/nutraceuticals2040026
|View full text |Cite
|
Sign up to set email alerts
|

Arctium lappa Lam. and Its Related Lignans Improve Hyperglycemia and Dyslipidemia in Diabetic Rodent Models: A Systematic Review and Meta-Analysis

Abstract: Research on nutraceuticals has focused on reducing the onset, progression, and significant consequences of diabetes mellitus. Arctium lappa Lam. is a great source of plant fibers and polyphenols that have anti-disease benefits, including those for diabetes mellitus. This study sought to determine the impact of Arctium lappa Lam. extracts and its associated lignans on diabetic hyperglycemia and dyslipidemia by conducting meta-analyses of the available research using diabetic rodents. English-language peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Burdock is also rich in vitamins B1, B2, C and A, and contains minerals including magnesium, sodium, potassium, calcium, zinc, copper, and iron. Based on the presence of active ingredients, multiple scientific studies have shown burdock to have prebiotic (inulin in the root) [9], antioxidant (caffeic acid in the stems, leaves, and rhizodermis) [10], antibacterial (betaeudesmol in the fruit) [11], and anticancer (tannin in the root, and arctin in the leaves, fruit and root) properties. In addition, burdock shows favorable dermatological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Burdock is also rich in vitamins B1, B2, C and A, and contains minerals including magnesium, sodium, potassium, calcium, zinc, copper, and iron. Based on the presence of active ingredients, multiple scientific studies have shown burdock to have prebiotic (inulin in the root) [9], antioxidant (caffeic acid in the stems, leaves, and rhizodermis) [10], antibacterial (betaeudesmol in the fruit) [11], and anticancer (tannin in the root, and arctin in the leaves, fruit and root) properties. In addition, burdock shows favorable dermatological properties.…”
Section: Introductionmentioning
confidence: 99%